(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To assess the satisfaction of medical staff at Andrology And Fertility Hospital Of Hanoi and some related factors. Methods: A descriptive cross-sectional study with analysis. Results: The overall satisfaction score of medical staff with the job is 3.58 ± 0.47 points. The overall satisfaction rate of medical staff is 56.2%. Factors related to the overall satisfaction of medical staff: Medical staff in the group with undergraduate and postgraduate training have a satisfaction rate 3.31 times higher than that of the group with training qualifications. In mid-level training, medical staff in the clinical sector had a satisfaction rate 2.48 times higher than that of the administrative group. Medical staff in the subclinical sector have a satisfaction rate 2.44 times higher than that of medical staff in the administrative division. The overall satisfaction rate of medical staff with working time of more than 5 years is 3.31 times higher than that of medical staff with working time from 6 months to 1 year. Conclusion: The overall satisfaction rate of medical staff is 56.2%, the overall satisfaction score is 3.58 ± 0.47 points. Factors related to general satisfaction include professional qualifications, work, and working time. Therefore, the hospital needs a support mechanism to increase the income of medical staff, organizes recruitment examinations to ensure regimes and policies for medical staff working at the hospital, and develop a plan, training support plan for medical staff working in the department.